Between Legal Certainty and Democratic Legitimacy: The Normative Void of the Constitutional Court Decision No. 135/PUU-XXII/2024 in Indonesia’s Constitutional System - Ikhsan Setiawan; Muchammad Daing Azimattara (Constitutionale, 2025)
General elections are the primary mechanism for realizing popular sovereignty under the 1945 Constitution of the Republic of Indonesia. Constitutional Court Decision No. 135/PUU-XXII/2024 marks a major shift in electoral design by separating national and regional elections, departing from the simultaneous model affirmed in Decision No. 55/PUU-XVII/2019. Although final and binding, the ruling creates a normative void due to the absence of transitional provisions. This study analyzes the constitutional implications of this paradigm shift, examines its consistency with prior jurisprudence, and evaluates regulatory transition options to preserve legal certainty and democratic legitimacy. Using a normative juridical method with conceptual and statutory approaches, the research finds that the divergence between the two decisions weakens legal certainty and risks institutional disruption, electoral disputes, and declining public trust ahead of the 2029 election. The case highlights tensions in the Court’s evolving role and underscores the urgent need for legislative action to establish clear transitional regulations to safeguard electoral stability and democratic legitimacy.